Histological, Histochemical And Immune Histochemical Study of Effect Aging on the Parotid Salivary Glands in Buffalo - Dhuha Adel Kareem1, Hiba M. Abd Alrahman1 , Fawzi-Alasadi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present work were carried out on twenty parotid salivary glands were collected from head of buffalo(slaughtering of Basra) and divided into two equal groups( one year age and five year age) . The results were showed that the parotid salivary gland consist of spherical serous acini connected with branched ducts, intercalated ducts which attached with striated ducts , these duct involved the intra lobular ducts. The larger duct named interlobular duct, myoepithelial cells located between the basal membrane and secretory acini and ducts. The results revealed that the effect of aging on the histological structures of parotid salivary gland by using routine stain, histochemical stain steriological histologically, and immunohistochemistry. The high intensity of connective tissues in the parotid salivary glands with age of five years as compared to the age of one years (normal intensity),also showed fibrosis in the parotid gland of five year age as compared with parotid gland of one year no appear any fibrosis, stereological histologically of the mean diameter of acini for parotid gland of five years age increased significantly p<0.05 (13±0.33 micron)while acini of one years age(10.4±0.02 micron), the mean diameter of intercalated duct for parotid gland of five years age increased significantly p<0.05 (40.13±2.61 micron) as compared of intercalated duct for age one years (26.56±1.22 micron). The histochemical results by using PAS stain showed low intensity of glycogen for parotid gland of five years age as compared to the group of one years age. The immuonohistochemistry (VEGF) showed decrease in the parotid salivary gland of five year age as compared to the group of one years age .